VERTICAL DISPLACEMENT MONITORING OF ZAKARPATTYA REGION TERRITORY BASED ON RADAR INTERFEROMETRY DATA - Uglitskih, E.; Vyzva, S.; Ivanik, Ivanik (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article presents result of deformation monitoring in Zakarpattya region, performed using the method of radar interferometry. The method of radar interferometry allows to monitor the displacements of the earth's surface in real time and quickly obtain up-to-date data. As a result of the research of the Carpathian model landfill, 26 pairs of interferograms for the period 2016–2018 were processed. As a result of these operations, a general map of vertical displacements of the earth's surface of the Carpathian model landfill was constructed. The territory is ranked into 3 zones according to the indicators of vertical displacements of the earth's surface. It is confirmed that the use of interferometry data is effective for detailed analysis of the regime and dynamics of dangerous geological processes. These surveys are of great value and with good resolution and appropriate processing algorithm give reasonable results and conclusions, which in combination with lithological-stratigraphic, geomorphological and structuraltectonic studies can be used to predict dangerous geological processes and minimize their negative impact on nature and man-made systems.
Keywords: remote sensing; interferometry; displacement of the earth's surface; dangerous geological processes